Peran Neurologi Pediatri Dalam Usaha Melawan Autisme - Saharso, Darto (Faculty of Psychology, Universitas Surabaya, 2005)
Though the prevalence is high, reaching 1 per 175 children, autism seems lacking attention and aduequate management, especially in Indonesia. The essence of autism as a disorder which could only be minimized/reduced but not cured certainly make parents of Autism Spectrum Disorder (ASD) patients more anxious. Information concerning the symptoms, controversy, and management of Autism patients and bystanding teachers in establishing education for Autism patients could not be separated from the participation of expert in pediatric neurology performing through biomedical therapies. Sekalipun memiliki prevalensi yang tinggi, mencapai 1 per 175 anak, autism ternyata belum memperoleh perhatian dan penanganan yang memadai, khususnya di Indonesia. Hakikat Autisme sebagai suatu gangguan yang hanya dapat diperbaiki namun tidak dapat disembuhkan tentu saja semakin menimbulkan kecemasan bagi para orang tua penderita Autism Spectrum Disorders (ASD). Pemberian informasi seputar gejala-gejala, kontroversi, dan penanganan penderita Autisme menjadi sesuatu yang semakin mendesak dan mutlak dibutuhkan. Kolaborasi intensif antara orangtua dan guru pendamping dalam upaya penyediaan pendidikan bagi anak penderika Autisme tidak dapat dilepaskan dari peran serta para ahli neurologi pediatric yang berkiprah melalui terapi biomedis.